An Analytical Study on the Use of Dark Patterns inCommerce: A Shariah and Ethical Perspective: DOI: https://doi.org/10.5281/zenodo.17006322 (Khairulummah, 2025)
In contemporary commerce, businesses increasingly employ dark patterns—deceptive design strategies intended to manipulate consumer behaviour and maximise profit. Common tactics include pre-ticked boxes, subscription traps, roach motels, and confirm shaming, which exploit consumer inattention or psychological pressure, compelling individuals to act against their genuine intent.From an Islamic legal and ethical standpoint, such practices raise serious concerns.The Qur’an explicitly prohibits unjust consumption of wealth, permitting trade only when conducted through mutual consent. Prophetic traditions (Hadith) further affirm that a sale is valid solely when founded upon genuine willingness.These principles underscore the centrality of transparency, justice, and voluntary agreement within Islamic commercial ethics.This study undertakes an analytical examination of dark patterns in light of Shariah and ethical frameworks, assessing their implications for consumer rights,market integrity, and social trust. The findings reveal that although these tactics may generate short-term corporate gains, they undermine fairness, violate consumer autonomy, and erode long-term trust in the marketplace. Consequently,from both Shariah and ethical perspectives, dark patterns are not only objectionable but impermissible, necessitating their abandonment in favour of commerce grounded in honesty, fairness, and informed consent.
Keywords: Dark Patterns, Consumer Rights, Shariah Compliance, Islamic Commercial Ethics, Transparency, Mutual Consent